Mimansa rules of interpretation and its applicability in the current legal system of India (Bhartiya Knowledge Systems, 2024)
The Mimansa rules of Interpretation were laid down by Jaimini in his Sutra around 600 BC and it can be considered to be one of the most scientific and rational which can even be utilised in present legal scenario. In spite of such rich traditional heritage, we Indians undervalued our own system and always run after the principles laid down by westerners such as Maxwell and Craies. In this article an attempt has been made to discuss the scientific and reasonable characteristics of this principle and the necessity of its application in the present legal system of India. Even if it is sparingly utilized by our Hon’ble Courts, it never failed to resolve disputes in a justifiable manner as done by our forefathers.